DARUS AS AN ANTI-CORRUPTION EDUCATION - Sholahuddin Al-Fatih (Association of Certified Fraud Examiners Indonesia Chapter, 2018)
Corruption is one of the biggest problems faced by developing countries, including Indonesia. A research conducted by Transparency International in 2016 shows that Indonesia is ranked 90th out of 176 countries in the world. This condition has caused many sectors to be disturbed. The Indonesian Corruption Eradication Commission (better known as KPK), an anti-corruption body officially established by the government, has recently been intervened by many parties. KPK has implemented various ways to eradicate corruption. One of them is through the channel of education by releasing Anti-Corruption Clearing House (ACCH) with the aim to provide anti-corruption education in schools. Unfortunately, ACCH gets less positive response from the public. Hence, this paper will discuss about the introduction of anti-corruption education from an early age through darus with the aim of preparing anti-corruption generation in Indonesia.